For the Record - Media as Nomoi - Angela Condello (Law Text Culture, 2018)
Scena. We are experiencing an explosion of recording (Ferraris 2015), which generates a proliferation of ontological and epistemological dimensions. For instance, our life here and now and our life in the datasphere (what we buy, when and why we were at the hospital, when we travel and with whom, etc.) today constitute two parallel dimensions intersecting and reciprocally defining each other (Floridi 2014). There is one Dr. AC buying milk, standing in front of a supermarket fridge on that date in that place, and there is one Dr. AC inhabiting the web through her publications, her visiting fellowships, and in the organisation of events, plus there is a patient, a mother, a daughter, etc. (the list made by John Searle is usually pretty long and contains all the functions we can have in the social world): the more that is recorded, the more can be traced back, and the more what we appear to be depends on how easily a datum can be found, iterated, re-interpreted. Technology, more than ever, is permanently producing and filling in a universal - almost infinite - archive, where information, transactions, communications (emails, telephone conversations, chats), intentions, mistakes and various other forms of human existence and traceability are contained.